STUDI TENTANG BATIK TANAH LIEK CITRA MANDIRI KECAMATAN SITIUNG KABUPATEN DHARMASRAYA PROVINSI SUMATERA BARAT - ERIT FAJRI, Drs. Erwin, M.Sn, Drs. Ir. Heldi, M.Si (Universitas Negeri Padang, 2015)
The purpose of this research was to (1) identify the term Batik Tanah Liek, (2) describe the forms of motives, and (3) describe the technique and process of making Batik Tanah Liek Citra Mandiri Kecamatan Sitiung. This was a qualitative research which applied descriptive approach. The source of the research was the product of Batik Tanah Liek (primary data) and library study (secondary data). The data were collected through observation, interview and documentation. The research findings revealed that the term Batik Tanah Liek was derived from the color of batik cloth which was the color of tanah liek (clay). The motives of Batik Tanah Liek Citra Mandiri Sitiung were in the form of geometric and were adopted from flora and fauna. Batik was made by using batik tulis technique. Batik was made in three phases covering preparation, pembatikan, and finishing.Kata Kunci : The term Batik Tanah Liek, forms of motives, technique and process